2018
DOI: 10.1111/dom.13472
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction is sufficient to increase GLP‐1 secretion, leading to improved left ventricular contractility and mitochondrial respiratory capacity

Abstract: Myocardial infarction causes rapid impairment of left ventricular function and requires a hypercontractile response of non-infarcted tissue areas to maintain haemodynamic stability. This compensatory adaptation is mediated by humoral, inflammatory and neuronal signals. GLP-1 is an incretin hormone with glucoregulatory and cardioprotective capacities and is secreted in response to nutritional and inflammatory stimuli. Inactivation of GLP-1 is caused by the ubiquitously present enzyme DPP-4. In this study, circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
(38 reference statements)
1
18
0
Order By: Relevance
“…Elevated GLP-1 levels during critical illness have been reported by previous studies [10,11,18]. These studies reported a 1.4- to 8-fold increase in GLP-1 levels and a 2- to 10-fold increase in IL-6 levels within 30 minutes to 6 hours depending on the study design [10,11,18].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Elevated GLP-1 levels during critical illness have been reported by previous studies [10,11,18]. These studies reported a 1.4- to 8-fold increase in GLP-1 levels and a 2- to 10-fold increase in IL-6 levels within 30 minutes to 6 hours depending on the study design [10,11,18].…”
Section: Discussionmentioning
confidence: 73%
“…GLP-1 is an incretin hormone that causes insulin secretion and suppresses glucagon production in the body [22]. Previous studies have shown that endogenous GLP-1 levels increase during critical illness, preceded by an early rise of IL-6 levels, and this independently predicts mortality [10,11,18,23]. Increased endogenous GLP-1 seems to be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secretion of PYY happens in response to nutritional stimuli from enteroendocrine L-cells located in the distal gut. The same cell population produces GLP-1 in response to nutritional but also inflammatory stimuli, leading to elevated GLP-1 levels in patients with acute myocardial infarction or sepsis [4,31]. Importantly, GLP-1 was found to be an excellent and independent predictor for future cardiovascular events or mortality in both groups of patients, demonstrating a relevant interaction between the cardiovascular system and the gut [5,32].…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have identified gastrointestinal hormones as modulators of cardiovascular risk. The gut-derived peptide GLP-1 was found to be secreted in response to acute myocardial infarction and to independently predict adverse outcome in this patient population [4,5]. Importantly, GLP-1 receptor agonists reduced cardiovascular events in high-risk patients with diabetes [6][7][8][9].…”
Section: Introductionmentioning
confidence: 91%